HIF1α mediates resistance to radiation and to KRAS inhibitors in pancreatic adenocarcinoma - Kevin J. Tu; Sanjit K. Roy; Tami J. Kingsbury; Hem D. Shukla (PLoS ONE, 2026)
Pancreatic ductal adenocarcinoma (PDAC) is highly treatment resistant and characterized by a hypoxic microenvironment. Here, we investigated the role of hypoxia-inducible factor 1α (HIF1α) in regulating resistance to radiation and KRAS-inhibitor. We employed CRISPR/Cas9 to knock out (KO) HIF1α from the murine KRAS G12D/+ ; p53 R172H/+ KPC and the KRAS G12D/+ ; p53 R273H ; CDK2NA -/- Panc-1 human pancreatic cell lines. Compared to WT, the HIF1α KO cell lines demonstrated a shift toward an epithelial phenotype and had decreased proliferation and migration under hypoxia. HIF1α KO cell lines were less likely to survive after radiotherapy, and neutral comet assays demonstrated DNA damage four hours after treatment, suggesting that HIF1α promotes radioresistance through non-homologous end joining. When treated with a KRAS G12D inhibitor, HIF1α KO cells exhibited significantly increased apoptosis due to decreased p53 degradation, likely mediated through Mdm2. Confirming this, enrichment of hypoxic signaling was associated with KRAS inhibitor resistance in a cohort of 31 KRAS G12D cell lines. Our results thus suggest that inhibiting HIF1α may sensitize PDAC to radiation and KRAS inhibitors. To explore this, we conducted a drug repurposing screen and identified three HIF1α inhibitors (bakuchiol, BAY-87–2243, 2-methoxyestradiol) whose sensitivities were correlated with sensitivity to Deltarasin, a KRAS inhibitor. Our findings suggest that HIF1α inhibitors could be used to sensitize PDAC to radiotherapy and KRAS inhibitors.